Formation of Shelf-Stable Pickering High Internal Phase Emulsion Stabilized by Sipunculus nudus Water-Soluble Proteins (WSPs) - Cao, Yupo; Dai, Yaping; Lu, Xuli; Li, Ruyi; Zhou, Wei; Li, Jihua; Zheng, Baodong (Frontiers in Nutrition, 2021)
To form a stable emulsion system, the water-soluble proteins (WSPs) of Sipunculus nudus were prepared as the sole effective stabilizer for the high internal phase emulsion (HIPEs), of which the influence of the WSPs concentration and environmental stability was investigated. The HIPEs were fabricated using a simple one-pot homogenization process (10,000 rpm/min, 3 min) that involved blending the WSPs (0.1, 1, 2, 3, 4, and 5 wt%) with soybean oil (60, 65, 70, 75, 80, 85, and 90%). The microstructure and properties of stable HIPEs were characterized by particle size, ζ-potential, visual observations, optical microscopy, and dynamic rheology property measurements. As the concentration of WSPs increases, the mean particle diameter of HIPEs decreases, on the contrary, the apparent viscosity and storage modulus gradually increase. At a given emulsifier concentration (3 wt%), the stable and gel-like HIPEs were formed at the oil internal phase (ϕ) values of 70–75%, all the pH range in values from 3 to 9, and the ionic strength from 100 to 500 mM. Furthermore, the HIPEs that were stabilized formed a gel-like state that was relatively stable to heat and storage (30 days). And there was a new phenomenon that the destabilized HIPE of the freeze-thaw treatments could still return to a gel-like state again after homogenizing. The study results suggest that the WSPs of S. nudus as a natural emulsifier could be widely used in the food industry.